2018
DOI: 10.3389/fimmu.2018.03027
|View full text |Cite
|
Sign up to set email alerts
|

Mas-Related G Protein-Coupled Receptor-X2 (MRGPRX2) in Drug Hypersensitivity Reactions

Abstract: The human ortholog MRGPRX2 and the mice ortholog, Mrgprb2 are activated by basic secretagogues and neurokinins. A number of commonly used small-molecule drugs (e.g., neuromuscular blocking agents, fluoroquinolones, vancomycin) have been recently shown to activate these receptors under in vitro experimental conditions, what results in mast cell degranulation. The above drugs are also known to cause IgE-mediated anaphylactic reactions in allergic patients. The new findings on mechanisms of drug-induced mast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
115
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 64 publications
0
115
1
2
Order By: Relevance
“…Anaphylaxis is a type-I IgE mediated allergic reaction caused by the activation of mast cells, whereas anaphylactoid reactions or pseudo-allergic reactions are non-immunologic sudden onset reactions mediated through the non-IgE pathway. The clinical symptoms of anaphylactoid shock, however, are similar to anaphylaxis [1]. Activation of mast cells by allergen or drugs causes a profound release of inflammatory mediators, which leads to anaphylactoid shock [2].…”
Section: Introductionmentioning
confidence: 99%
“…Anaphylaxis is a type-I IgE mediated allergic reaction caused by the activation of mast cells, whereas anaphylactoid reactions or pseudo-allergic reactions are non-immunologic sudden onset reactions mediated through the non-IgE pathway. The clinical symptoms of anaphylactoid shock, however, are similar to anaphylaxis [1]. Activation of mast cells by allergen or drugs causes a profound release of inflammatory mediators, which leads to anaphylactoid shock [2].…”
Section: Introductionmentioning
confidence: 99%
“…MRGPRX2 is mostly associated with the tryptase/chymase positive MCs (MC TC ) that are predominant in the skin [14,15,27]. MRGPRX2 can be activated by various peptides encompassing drugs, antimicrobial peptides, and neuropeptides like Substance P (SP), making the receptor quite universal [17,19,28]. While thimerosal caused footpad swelling under local injection in wild-type mice, we found that neither mast celldeficient mice nor MrgprB2-knockout mice responded to local thimerosal injection.…”
Section: Discussionmentioning
confidence: 87%
“…MRGPRX2, a member of the Mas-related gene family, was found to be expressed in sensory neurons of dorsal root ganglia, mast cells, and keratinocytes [17]. Its ortholog in mouse is MrgprB2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leysen et al suggested that quantification of specific IgE [6,7]. In a recent animal study, it was shown that NMBA activates mast cell degranulation through Mas-related G-protein-coupled receptor member X2 (MRGPRX2) activation independent of the presence of IgE antibodies [14,15]. Activation of this receptor induces a non-IgEmediated response in NMBA-naïve patients such as a pseudo-allergic reaction.…”
Section: Discussionmentioning
confidence: 99%